Length Scale Parameterization and Stability Analyses With Different Statistical Methods in Wind Measurements - Tuna, Faruk; Bingöl, Ferhat (Izmir Institute of Technology, 2018)
When there is an attempt to find vertical wind speed and temperature profile in the absence of stability analysis then the bias is observed in those profiles. Wind profile shape can be estimated from the logarithmic wind speed formula under neutral condition since the diabatic stability term omits at that time and on the contrary, for other stability classes, this term should be derived by numerically or analytically, otherwise, the bias will be increased for wind speed and vertical temperature profiles. In this study, the goal is to give different models and options for the masts where stability analysis can’t be done by using data where comes from conventional masts. Here, different 2 kinds scenarios will be given to see better: Scenario 1: No stability analysis applied. Conventional mast measurements are used where the wind speed measurements are at two different heights, the temperature is from only one location, and wind direction measurements are from wind vanes. Therefore, unwanted occasions occur such as overestimate and underestimate for unstable and stable conditions, respectively. Scenario 2: Stability analysis applied by using the sonic anemometer which provides high-frequency data and vertical wind velocity. After determining diabatic wind term, wind speed can be corrected by implementing diabatic term into profile equation. As a summary, those two scenarios are compared and in order to get correct measurements different models for the conventional masts are given.

Stabilite analizi yokluğunda dikey rüzgar hızı veya sıcaklık profili bulma girişimi olduğunda bu profillerde yanılmalar görülür. Rüzgar profili normal koşullar altında diabatik terim olmadığı için logaritmik rüzgar hızı formülü ile bulunabilir ve bunun aksine kararlı ya da kararsız durumlarda nümerik veya analitik olarak elde edilir. Yoksa dikey rüzgar hızı ve sıcaklık profillerinde yanılmalar olacaktır. Bu çalışmada ana amaç geleneksel ölçüm cihazlarından gelen datalarla stabilite analizinin yapılmadığı yerlerde kullanılabilecek farklı modeller ve seçenekler sunmaktır. Burada, daha iyi anlamak için 2 farklı senaryo verilecektir: Senaryo 1: Kararsızlık analizi yok. 2 farklı yükseklikten rüzgar hızı ölçümü yapıldığı, sıcaklığın ise tek bir noktadan alındığı, ve rüzgar yönlerinin rüzgar güllerinden alındığı geleneksel ölçüm direkleri kullanılmaktadır. Bu yüzden, kararsız ve kararlı durumlar için sırasına göre abartılı ya da olması gerekenden az hesaplanması gibi istenmeyen durumlar meydana gelmektedir. Senaryo 2: Yüksek frekanslı ve dikey hız ölç ümlerini sağlayan sonik anemometreler kullanılarak kararsızlık analizi yapılabilir. Diabatik hız terimi elde edildikten sonra profil denklemleri içine koyularak rüzgar hızında düzeltmeler yapılır. Sonuc¸ olarak bu 2 senaryo kıyaslanmakta ve doğru ölçümler elde etmek için geleneksel direkler için farklı modeller verilmektedir.
Rüzgar Ölçümlerinde Farklı İstatistiki Metotlarla Yüzey Katmanı Derecelendirmesi ve Karasızlık Analizi
Thesis (Master)--Izmir Institute of Technology, Energy Engineering, Izmir, 2018
Includes bibliographical references (leaves: 54-57)
Text in English; Abstract: Turkish and English
Keywords: Atmospheric boundary layer; Wind measurements; Remote sensors; Temperature profile